2017
DOI: 10.24815/siele.v4i2.6104
|View full text |Cite
|
Sign up to set email alerts
|

Implementation of classroom management by English teachers at high schools in Jambi, Indonesia

Abstract: This study was aimed at analyzing the implementation, processes and problems of classroom management in two

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 7 publications
(21 reference statements)
1
9
0
1
Order By: Relevance
“…The teachers' challenges in the classroom management practice during the implementation of 2013 Curriculum in this study were in line with a study by Habibi et al (2017) about implementation of classroom management by English teachers at high schools in Jambi. Their study revealed that time-consuming was one of the problems in the seating arrangements experienced by the teachers among other problems such as big number of students in the classroom and small size of the classroom to move the chairs and tables around.…”
Section: The Vocational High School English Teachers' Challenges In the Classroom Management Practicesupporting
confidence: 84%
See 1 more Smart Citation
“…The teachers' challenges in the classroom management practice during the implementation of 2013 Curriculum in this study were in line with a study by Habibi et al (2017) about implementation of classroom management by English teachers at high schools in Jambi. Their study revealed that time-consuming was one of the problems in the seating arrangements experienced by the teachers among other problems such as big number of students in the classroom and small size of the classroom to move the chairs and tables around.…”
Section: The Vocational High School English Teachers' Challenges In the Classroom Management Practicesupporting
confidence: 84%
“…The limitation of time for administering the assessment and the complexity of the items (Febry, 2017) as well as the quite large size of class (Ahmad, 2014) are the factors that make them difficult in implementing the authentic assessment. In the classroom management practice, Habibi et al (2017) conduct a qualitative study that reveals the problems such as lack of knowledge among English teachers regarding the latest technology, lack of up-to-date school facilities, large number of students in each class, lack space in the classroom, less opportunity for the students to practice (because the classes were too big), and situational problems, i.e. crowding in some classes.…”
mentioning
confidence: 99%
“…This might provide a great pressure for the teachers to accomplish their lessons. The current study suggests to ideally have 20-25 students within 5-6 groups to guide them (Habibi, Mukminin, Sofwan, & Sulistiyo, 2017). Thereby, such a process may reduce their stress levels and tensions during the lesson.…”
Section: The Educational Support From Classroom Populationmentioning
confidence: 97%
“…Anchored by the aforementioned rationales, the purposes of this case study are to examine (1) what complexities the teachers encounter in the context of classroom management and (2) what strategies they employ to deal with such problems during their classes. A recent study about classroom management in the Indonesian context has been previously carried out by Habibi et al (2017Habibi et al ( , 2018 who listed six emerging issues related to classroom management, including (1) teachers' attitudes toward new technology for teaching, (2) schools' inadequate equipment, (3) too many students, (4) small rooms, (5) students' insufficient amounts of practice, and (6) too many students. However, these studies have yet to specifically focus on foreign language education in remote areas.…”
Section: Exploring Efl Teachers' Classroom Managementmentioning
confidence: 99%
“…These factors are critical for investigation in the teacher education context. Although previous studies have explored classroom management in schooling sectors (Habibi et al, 2017;, unfortunately, they have not specifically discerned foreign language learning in remote areas such as English language teaching. Thereby, this study seeks to investigate remote areas EFL classroom management.…”
Section: The Current Condition Of Schools In Remote Areas Of Indonesiamentioning
confidence: 99%